2009
DOI: 10.1111/j.1479-828x.2009.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of psychosocial support during childbirth in Ibadan, south‐west Nigeria: A randomised controlled trial

Abstract: Objective:To assess the effect of psychosocial support on labour outcomes. Methodology: A randomised control trial conducted at the University College Hospital Ibadan, Nigeria, from November 2006 to 30 March 2007. Women with anticipated vaginal delivery were recruited and randomised at the antenatal clinic. The experimental group had companionship in addition to routine care throughout labour until two hours after delivery, while the controls had only routine care. The primary outcome measure was caesarean sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 25 publications
2
40
0
2
Order By: Relevance
“…Our study was one of the first trials of a facility-based intervention to involve male partners in maternity care in sub-Saharan Africa that did not evaluate the prevention of mother-to-child HIV transmission 17 , 18 . We found that even a simple educational intervention involving a maximum of three contacts can be beneficial.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our study was one of the first trials of a facility-based intervention to involve male partners in maternity care in sub-Saharan Africa that did not evaluate the prevention of mother-to-child HIV transmission 17 , 18 . We found that even a simple educational intervention involving a maximum of three contacts can be beneficial.…”
Section: Discussionmentioning
confidence: 83%
“…Consequently, the impact of these strategies is not clear. Few high-quality experimental studies have been conducted in sub-Saharan Africa and even fewer have assessed facility-based interventions, 17 , 18 apart from those focusing on the prevention of mother-to-child HIV transmission 19 …”
Section: Introductionmentioning
confidence: 99%
“…This fact may contribute to changes related to gender and family issues, as well as transformations in the constructed values about the birth event. [16][17] In addition, it allows the construction of care respectful to human life and the family, and can promote greater family interaction and strengthening of bonds. [17][18] The information about the rules and routines of the obstetrical center, provided to the companion at the time of the parturient's hospitalization, are extremely important to guide him during his stay in the sector.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17] In addition, it allows the construction of care respectful to human life and the family, and can promote greater family interaction and strengthening of bonds. [17][18] The information about the rules and routines of the obstetrical center, provided to the companion at the time of the parturient's hospitalization, are extremely important to guide him during his stay in the sector. However, sometimes they may not be enlightening enough, and in others, the companion may have difficulty assimilating them because of being emotionally involved and/or needing to "solve" personal problems or problems to hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation